The Strengthening Fraud Prevention in Higher Education: An Empirical Study of Internal Control System and Good University Governance - Rudiawie Larasati; Heru Tjaraka (Qubahan Academic Journal)
This research investigates how internal control systems and Good University Governance (GUG) influence fraud prevention in higher education institutions in Eastern Indonesia. Various instances of fraud in Indonesian universities have been attributed to the Internal Supervisory Unit (SPI), which plays a crucial role in enforcing GUG. The study adopts a quantitative approach with purposive sampling to analyze a mediating model involving internal control systems, fraud prevention, and GUG. Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method was employed for data analysis. The findings demonstrate that both GUG and the implementation of internal control systems significantly contribute to fraud prevention. Moreover, the research highlights the indirect effect, where GUG acts as a mediator between internal control systems and fraud prevention. The results emphasize the importance of incorporating robust governance practices to reduce fraud in educational institutions in Indonesia.